The influence of skin thickness on the determination of the percentage of body fat (skinfolds and ultrasound) - Breytenbach, Johannes Gerhardus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human Movement Studies)--University of Stellenbosch, 1996.